ANALISIS PENGEMBANGAN WIRAUSAHA LOKAL MELALUI SEKTOR EKONOMI BASIS INDUSTRI KECIL MENENGAH (IKM) DI KABUPATEN KAMPAR - eka armas pailis (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: This study aims to identify the sectors of the local entrepreneurial base in Kamparand other types of local entrepreneurs and their superior characteristics of the role andactivities. One solution poverty alleviation programs in Kampar. The method used descriptivequantitative primary data based on random sampling and conducted a survey of 30 SMEs andanalyzed using an approach LQ (Location Quitients). Kampar based on analysis of LQ has abase sectors in the form of sectors of agriculture, mining and quarrying, and constructionsector. Entrepreneurial types that can be developed in Kampar as follows: a. Fisheriesderivative products, namely smoked catfish, catfish nuggets, shredded catfish, meatballs,catfish, salted catfish, fish crackers and other fish derived products. b. Palm oil derivativeproducts, such as cooking oil, salad oil, soap, ice cream, margarine and others. c. Productsderived from tropical fruits such as jackfruit chips, pineapple chips; jams, fruit dodol, syrup,pollen, canned fruits. d. Other products that can be developed is a blacksmith and traditionalcakesKeywords: Local Entrepreneurial Development, Sector Basis SME Industry